2, 4‐dinitroanisole transformation during advanced oxidation with ultraviolet light emitting diodes and hydrogen peroxide. (17th September 2022) - Burdsall, Adam C.; Schober, Jaya Das; Stubbs, John E.; Agrawal, Abinash; Harper, Willie F.
Abstract: This study investigated the kinetics and reaction mechanisms associated with advanced oxidation of 2, 4‐dinitroanisole (DNAN) with light emitting diodes (LEDs) in the UV/H2 O2 process. The pseudo first‐order reaction rate constants for DNAN oxidation depended on the H2 O2 /DNAN molar ratio and were between 0.017 and 0.026 min −1 . Hydroxyl radical scavenging was strongly implicated by the experimental results. High mass spectrophotometric chromatograms showed the presence of several by‐products, including three with ecotoxicity that is greater than that of DNAN. Transformation pathways were analysed using Density Functional Theory (DFT), which helped to predict the presence of experimentally detected DNAN by‐products by considering Mulliken charges. This study is the first to elucidate DNAN transformation mechanisms using both experimental studies and computational chemistry.